Revamping sustainable strategies for hyper-local restaurants: A multi-criteria decision-making framework and resource-based view - Muneeb, F. (2023)
There is a growing emphasis on sustainability within the hospitality industry. However, research on hyper-local restaurants’ strategic sustainable strategies is scarce. Accordingly, this study aims to unveil the hyper-local Chinese restaurateurs' critical success factors (CSFs). Grounded on the CSFs identified in the literature and validated by experts, data were collected from hyper-local restaurant owners and analysed through multi-criteria decision-making (MCDM), best-worst method (BWM), and hesitant fuzzy shapely order weights average (HSFOWA) approach. Results suggest that green entrepreneurial orientation is symbiotic, and green customer education, ability, motivation, capability, entrepreneurial orientation, and high-commitment work practices significantly impact the sustainability of hyper-local restaurants. Findings stimulate sustainable strategies based on available CSFs. Practical and managerial implications are discussed.